Extractive Spectrophotometric Method for Determination of Molybdenum in Steels and Environmental Samples - Rameshwar Dass; Jitander K. Kapoor; Sunita Gambhir (Journal of Chemistry)
An extractive spectrophotometric method has been developed for microdetermination of molybdenum. At room temperature Mo(VI) was reduced to Mo(V) in 2 M H2SO4 using ascorbic acid as a reductant. The Mo(V) formed a yellow-coloured (1 : 2) complex with 6-chloro-3-hydroxy-2-(3′-hydroxyphenyl)-4-oxo-4H-1-benzopyran (CHHB). The complex was quantitatively extracted into toluene and absorbed maximum at λmax 404 nm. Beer’s law was obeyed over the concentration range of 2.31 μg Mo ml−1 with a molar absorptivity and Sandell's sensitivity of 5.62×104 L mol−1 cm−1 and 0.0016 μg Mo cm−2, respectively. The relative standard deviation was 0.0025 (in absorbance units) for 10 replicate determinations of 1 μg Mo ml−1. The method was free from the interference of large number of analytically important elements. Molybdenum has been determined satisfactorily in different technical, synthetic, and environmental samples with improved accuracy and precision.